Towards strength–ductility balance in a Ti-6Al-4V alloy through microstructure optimization by composite hot forging and two-step annealing processes - Jiang, Shenshi; Zhang, Guangqing; Zhu, Lisong; Wang, Qian; Qu, Feijun; Wang, Jun; Lu, Yao; Han, Jian (Oxford University Press (OUP), 2025)
Objectives Obtaining strength–ductility balance in titanium alloys remains a challenge to this day. In this work, we improve the strength–ductility synergy of a Ti-6Al-4V alloy through specialized hot forging and two-step annealing processes. Methods During hot forging, the large equiaxed grains undergo minimal change, while all the lamellar α grains spheroidize to fine equiaxed grains due to severe dynamic recrystallization. During subsequent annealing and water quenching, the large equiaxed grains remain unchanged, and the martensite transformation occurs within fine equiaxed grains, leading to the microstructures composed of large equiaxed grains and nanosized acicular α′ martensite grains in the water quenched (WQ) alloy. Results and conclusion Compared to the hot forged (FG) alloy, the WQ alloy exhibited a significantly increased tensile strength and a decreased elongation. The strengthening effect came from the high dislocation density, high-density grain boundaries, and dense twin boundaries in the region of α′ martensite. The short-time annealed (ST) alloy after the second-step short-time annealing then showed a similar grain size and morphology to the WQ alloy. However, the dislocation density in large equiaxed grains dramatically decreased. This caused an increased elongation without sacrificing strength compared with the WQ alloy, implying the superior strength–ductility balance.
Keywords: 40 Engineering; 4016 Materials Engineering; titanium alloy; cold-stretching; αþα0 nanostructure; α0 nano twins; strength–ductility synergy